Lithium Protects Against Spinal Cord Injury in Rats: Role of Nitric Oxide - Zakeri, Marjan; Afshari, Khashayar; Gharedaghi, Mohammad Hadi; Shahsiah, Reza; Rahimian, Reza; Maleki, Farid; Dehpour, Ahmad Reza; Javidan, Abbas Norouzi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Objective Lithium improves locomotor scores after spinal cord injury (SCI) in rats. However, the underlying mechanisms are unknown. Herein, we assess the role of nitric oxide (NO) in this action.Methods The first set of experiments were performed to determine a dose of lithium that effectively improves locomotor scores in rats with SCI. Therefore, rats received different doses of lithium chloride (1, 4, 10, and 20 mg/kg intraperitoneally) or saline 1 hour before SCI. In the next step, the role of NO in the effect of lithium on SCI was investigated. For this purpose, rats were co-treated with an effective dose of lithium (20 mg/kg 1 hour before SCI) and a noneffective dose of Nω-nitro-L-arginine methyl ester (L-NAME, a nonselective NO synthase inhibitor; 15 mg/kg intraperitoneally 30 minutes before SCI). SCI was induced by compressing the T9 spinal segment with an aneurysmal clip for 60 seconds in anesthetized rats. Locomotor scores were determined at 1, 3, 5, 7, 14, 21, and 28 days after SCI. Plasma lithium levels were measured 12 hours after SCI. Spinal histopathologies were examined 30 days after SCI.Results Lithium (20 mg/kg) significantly improved locomotor scores and decreased histopathologic spinal damage. l-NAME (15 mg/kg) reversed the beneficial effects of lithium. The 20-mg/kg dose of lithium resulted in a 0.68 ± 0.02 mEq/L plasma lithium concentration, which is lower than the therapeutic level in humans (0.8–1.2 mEq/L).Conclusion Lithium protects against SCI through an NO-dependent mechanism.
Keywords: lithium; nitric oxide; Nω-nitro-l-arginine methyl ester; spinal cord injury; rat